Genome-wide aberrant methylation in primary metastatic UM and their matched metastases - Kyra N. Smit; Ruben Boers; Jolanda Vaarwater; Joachim Boers; Tom Brands; Hanneke Mensink; Robert M. Verdijk; Wilfred F. J. van IJcken; Joost Gribnau; Annelies de Klein; Emine Kilic (Scientific Reports, 2022)
Abstract Uveal melanoma (UM) is an aggressive intra-ocular cancer with a strong tendency to metastasize. Metastatic UM is associated with mutations in BAP1 and SF3B1, however only little is known about the epigenetic modifications that arise in metastatic UM. In this study we aim to unravel epigenetic changes contributing to UM metastasis using a new genome-wide methylation analysis technique that covers over 50% of all CpG’s. We identified aberrant methylation contributing to BAP1 and SF3B1-mediated UM metastasis. The methylation data was integrated with expression data and surveyed in matched UM metastases from the liver, skin and bone. UM metastases showed no commonly shared novel epigenetic modifications, implying that epigenetic changes contributing to metastatic spreading and colonization in distant tissues occur early in the development of UM and epigenetic changes that occur after metastasis are mainly patient-specific. Our findings reveal a plethora of epigenetic modifications in metastatic UM and its metastases, which could subsequently result in aberrant repression or activation of many tumor-related genes. This observation points towards additional layers of complexity at the level of gene expression regulation, which may explain the low mutational burden of UM.